(untitled) (Revista Estudios Psicológicos, 2022)
The subject of euthanasia in Colombia is full of opinions and discussions regarding its approval and practice, being this decision very controversial due to its legal, ethical, moral, religious and cultural implications. The objective of this study is to know the role of psychology professionals in the process of patients who request the euthanasia procedure. This research is focused on the qualitative paradigm of descriptive scope of documentary type where primary and secondary sources of information on the subject were analyzed. It can be concluded that the interventions of mental health professionals are essential at each stage of the life course of people undergoing the euthanasia process, in addition to helping in the rough road of the family’s grief.